Critical path method tutor for construction planning and scheduling - East, E. William (McGraw-Hill's AccessEngineering., 2015)
This unique tool provides a fresh approach to construction scheduling by focusing on ways in which the Critical Path Method (CPM) can be used to manage construction project schedules to meet today's ever-increasing demands to improve operational efficiency and increase profitability.